2019
DOI: 10.1097/aog.0000000000003054
|View full text |Cite
|
Sign up to set email alerts
|

Primary Small Cell Neuroendocrine Tumor Within a Urethral Diverticulum

Abstract: BACKGROUND: Primary small cell neuroendocrine carcinoma of the urinary tract is a very rare cancer, accounting for fewer than 0.5% of urinary tract tumors. These are aggressive neoplasms with high rates of metastases. Urethral diverticula can be found in up to 6% of women. CASE:A 31-year-old woman presented with a clear vaginal discharge and an anterior vaginal wall mass that was thought to be a recurrent cyst. After surgical dissection, she was noted to have a urethral diverticulum with a solid nodule at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…4). Among previously reported nine cases of urethral neuroendocrine tumors, these cases had the history of bladder cancer 4–12 . Thus, the pathogenesis of neuroendocrine urethral tumor might be associated with the history of bladder cancer.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…4). Among previously reported nine cases of urethral neuroendocrine tumors, these cases had the history of bladder cancer 4–12 . Thus, the pathogenesis of neuroendocrine urethral tumor might be associated with the history of bladder cancer.…”
Section: Discussionmentioning
confidence: 93%
“…3 There have been only nine reported cases of urethral neuroendocrine tumors, which are extremely rare. [4][5][6][7][8][9][10][11][12] The origin of neuroendocrine tumors arising in the urinary tract is not clear. 13 Urothelial carcinoma may differentiate as a neuroendocrine tumor because it has been reported that cancerous transformation of multipotent epithelial cells in transitional epithelial cells may become a neuroendocrine tumor and that transitional epithelial cells themselves may have neuroendocrine differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most common urethral-cancer histological subtypes are urothelial, squamous-cell carcinoma (SCC), and adenocarcinoma [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Since urethral cancer has been studied in very small patient groups, only more historical studies as well as case reports have focused on other unconventional histological subtypes, instead of urothelial, SCC, and adenocarcinoma of the urethra [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. To the best of our knowledge, no previous investigation compared different unconventional urethral-cancer histologies.…”
Section: Introductionmentioning
confidence: 99%